Combined Effects of Experimental Acidification and Eutrophication on Reef Sponge Bioerosion Rates - Webb, Alice E.; van Heuven, Steven M. A. C.; de Bakker, Didier M.; van Duyl, Fleur C.; Reichart, Gert-Jan; de Nooijer, Lennart J. (Frontiers in Marine Science, 2017)
Health of tropical coral reefs depends largely on the balance between constructive (calcification and cementation) and destructive forces (mechanical-chemical degradation). Gradual increase in dissolved CO2 and the resulting decrease in carbonate ion concentration ('ocean acidification') in ocean surface water may tip the balance towards net mass loss for many reefs. Enhanced nutrients and organic loading in surface waters (‘eutrophication’), may increase the susceptibility of coral reef and near shore environments to ocean acidification. The impacts of these processes on coral calcification have been repeatedly reported, however the synergetic effects on bioerosion rates by sponges are poorly studied. Erosion by excavating sponges is achieved by a combination of chemical dissolution and mechanical chip removal. In this study, Cliona caribbaea, a photosymbiont-bearing excavating sponge widely distributed in Caribbean reef habitats, was exposed to a range of CO2 concentrations, as well as different eutrophication levels. Total bioerosion rates, estimated from changes in buoyant weights over 1 week, increased significantly with pCO2 but not with eutrophication. Observed chemical bioerosion rates were positively affected by both pCO2 and eutrophication but no interaction was revealed. Net photosynthetic activity was enhanced with rising pCO2 but not with increasing eutrophication levels. These results indicate that an increase in organic matter and nutrient renders sponge bioerosion less dependent on autotrophic products. At low and ambient pCO2, day-time chemical rates were ~50% higher than those observed at night-time. A switch was observed in bioerosion under higher pCO2 levels, with night-time chemical bioerosion rates becoming comparable or even higher than day-time rates. We suggest that the difference in rates between day and night at low and ambient pCO2 indicates that the benefit of acquired energy from photosynthetic activity surpasses the positive effect of increased pCO2 levels at night due to holobiont respiration. This implies that excavation must cost cellular energy, by processes such as ATP usage for active Ca2+ and/or active proton pumping. Additionally, competition for dissolved inorganic carbon species may occur between bioerosion and photosynthetic activity by the symbionts. Either way, the observed changing role of symbionts in bioerosion can be attributed to enhanced photosynthetic activity at high pCO2 levels.